BENTUK AKULTURASI ESTETIKA ISLAMI DAN MUSIK POPULER DALAM PERTUNJUKAN SALAWAIK DULANG GROUP ARJUNA MINANG - Robby Suhendra; Ediwar Ediwar; Andar Indra Sastra (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT This writing aims at revealing the acculturation of Islamic aesthetics and popular music in salawaik dulang performance. Salawaik (salawat) literally means praise or adulation toward Prophet Muhammad SAW; dulang is a bronze vessel commonly used as means of serving drinks or as big plate in the ceremony of makan bajamba. Salawaik dulang is religious song that uses dulang as rhythm arranger and also functions as music instrument in salawaik dulang performance. Problem discussed in this writing is religious values packed together with popular music in salawaik dulang performance. Keywords: acculturation, Islamic aesthetics, popular music, salawaik dulang